2020
DOI: 10.1002/chem.201904499
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Deactivation: Classical and Emerging Strategies for Efficient Stabilization of Molecular Electrocatalysts

Abstract: Development of highly active molecular electrocatalysts for fuel-forming reactions has relied heavilyo nu nderstanding mechanistic aspects of the electrochemical transformations.C areful fine-tuning of the ligand environment oriented mechanistic pathways towards highera ctivity and optimal product distribution for several catalysts. Unfortu-nately,m anyc atalysts deactivate in bulk electrolysis conditions, diminishing the impact of the plethora of highly tuned moleculare lectrocatalytic systems. This Minirevie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…1b). 45,66,67 Although a number of water-soluble molecular catalysts for CO 2 RR have been reported so far, [68][69][70][71] the electrode functionalization approach allows to overcome the solubility limitations in aqueous electrolytes often reported for homogeneous catalysts (most of them are soluble in organic solvents or organicwater mixtures), and helps to facilitate the catalyst recycling and the separation of liquid CO 2 RR products. Moreover, the physicochemical interactions at the catalyst-electrode interface may induce drastic reactivity changes, including altering the conventional reaction pathways occurring in the homogeneous phase.…”
Section: Co 2 Rr Catalysts Based On Transition Metalsmentioning
confidence: 99%
“…1b). 45,66,67 Although a number of water-soluble molecular catalysts for CO 2 RR have been reported so far, [68][69][70][71] the electrode functionalization approach allows to overcome the solubility limitations in aqueous electrolytes often reported for homogeneous catalysts (most of them are soluble in organic solvents or organicwater mixtures), and helps to facilitate the catalyst recycling and the separation of liquid CO 2 RR products. Moreover, the physicochemical interactions at the catalyst-electrode interface may induce drastic reactivity changes, including altering the conventional reaction pathways occurring in the homogeneous phase.…”
Section: Co 2 Rr Catalysts Based On Transition Metalsmentioning
confidence: 99%
“…15 Thus, to overcome these issues, novel strategies for the heterogeneous stabilization of molecular WOCs on solid surfaces have been developed. 155 The main goals include (i) preserving the intrinsic activity and selectivity, (ii) stabilization of intermediate species, and lowering the energy barrier while facilitating O-O bond formation, (iii) tuning the catalyst loading to lower the water oxidation overpotentials, (iv) attaining facile electron transfer kinetics at the interface, and (v) promoting long-term resilience against leaching and highly oxidative media. 15,23,38 All this must be complemented with the optimization of surface area/ morphology, hydrophobicity and hydrophilicity, density of active metal sites, and mass/charge transfer properties.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…Particularly, the stabilization of molecular WOCs by tuning the electronic/steric properties of the ligand requires meticulous screening since the nature of the ligand can affect their activity and selectivity. 155,156 Recently, N,N 0 -bidentate electronically asymmetric ligands were used to stabilize low-valent transient Co I species. 157 The results showed that electron-deficient ligands removed electron density from the Co sites, thereby preventing deactivation of the catalyst, and stabilizing the complex (Fig.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…Heterogenizing molecular catalysts can enhance both the activity and turnover number (TON), up to several orders of magnitude, by improving the electron transfer kinetics and overall catalyst utilization. 11 In addition, catalyst loading can be judiciously controlled to isolate active sites and prevent catalyst deactivation by inhibiting side reactions such as dimerization and catalyst poisoning. One of the earliest catalyst immobilization strategies involves noncovalent interactions (van der Waals, π–π stacking, and electrostatic) between the molecular catalyst and the electrode material.…”
Section: Introductionmentioning
confidence: 99%